Attitudes and behavior towards patient safety in an operating room - María del Pilar Sánchez Moreno; Francisca Moreno Medina; José Joaquín Barrajón Martín de la Sierra; Margarita Romero Taboada (Fundación para el Desarrollo de la Enfermería, 2013)
Patient´s safety is a priority line of action in the Quality of Health Care. Adequate patient safety culture is one of the important pillars in the health care. Also the World Health Organization reports that 7 million people, of 234 million of major surgeries, suffer complications and this can be reduced by half with a system that decreases the possibility of error. Objectives: To determinate the attitude and behavior of professionals in the operating room unit in Hospital Virgen de la Salud of Toledo towards patient safety. Material and method: The type of study is a descriptive and transversal. Population: medical and nursing staff of the theatre with over 1 year in service. Measurement of variables will be made by a validated test and adapted to Spanish territory by the Agency for Healthcare Research and Quality of the United States. We intend to identify the strengths and weaknesses in matter of operating room safety, to know the starting point for the implementation of the surgical safety checklist and to develop a safety culture in the operating room with standardized tools and regular quality controls.